2018
DOI: 10.1108/s1569-376720180000019002
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 1 Investigating International Portfolio Diversification Opportunities for the Asian Islamic Stock Market Investors

Abstract: The purpose of this chapter is to analyze the possible portfolio diversification opportunities between Asian Islamic market and other regions' Islamic markets; namely USA, Europe, and BRIC. This study makes the initial attempt to fill in the gaps of previous studies by focusing on the proxies of global Islamic markets to identify the correlations among those selected markets by employing the recent econometric methodologies such as multivariate generalized autoregressive conditional heteroscedastic-dynamic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Therefore, Dow Jones Islamic indexes are cointegrated and have a long run association. This result is similar to those of Yildirim and Masih (2018) who found that US, Asia, Europe, BRIC markets are highly correlated yielding minimal diversification benefits. Our eight indexes prices move together.…”
Section: Methodssupporting
confidence: 89%
“…Therefore, Dow Jones Islamic indexes are cointegrated and have a long run association. This result is similar to those of Yildirim and Masih (2018) who found that US, Asia, Europe, BRIC markets are highly correlated yielding minimal diversification benefits. Our eight indexes prices move together.…”
Section: Methodssupporting
confidence: 89%
“…(Oertel et al, 2022)The risk management of transitory risk for tangible assets has gained significant interest among researchers and market participants, especially in the past ten years. (Yildirim & Masih, 2018) The findings indicate that Asian investors have better portfolio diversification opportunities with the US markets, followed by the European markets. (Sosa et al, 2019), our study analyzes the volatility of Bitcoin by employing and comparing symmetric and asymmetric GARCH model extensions (threshold ARCH (TARCH) and exponential GARCH (EGARCH)).…”
Section: Introductionmentioning
confidence: 95%